Development of Observer State Output Feedback for Phase-Shifted Full Bridge DC-DC Converter Control - Ibrahim, O. (Institute of Electrical and Electronics Engineers Inc., 2017)
Controllers are designed to regulate output voltage and improve dynamic performance of dc-dc converter to variable supply voltage, load current or circuit element variation. Conventional controller like PID has narrow dynamics that limit its application to quiescent supply input voltage and load current change. Recent research efforts are exploiting state of the art power electronics devices and high computational speed digital signal processor to improve transient and dynamics performance of power converters through advanced modern control techniques. This paper presents a design and evaluation of observer state output feedback controller for phase-shifted full bridge zero voltage switching dc-dc converter output voltage regulation to widen the supply input voltage. The converter closed-loop control was implemented in MATLAB/Simulink environment and the results demonstrated improved transient response to wider supply voltage and sudden load current change as compared with the conventional PID controller. © 2013 IEEE.